BADANIA KLINICZNE I DOŚWIADCZALNE W CHOROBACH SERCA, PŁUC I NACZYŃThe impact of biofilm formation by Gram-positive bacteria on patient outcome following cardiac surgery - Bilewska, Agata; Łopaciuk, Urszula; Młynarczyk, Grażyna; Młynarczyk, Andrzej; Trafny, Elżbieta; Kołsut, Piotr; Kocańda, Szymon; Kuśmierczyk, Mariusz; Różański, Jacek M. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background: The ability of biofilm formation occurs among both Gram-positive and Gram-negative bacteria. Biofilm is a structured community of bacterial cells enclosed in a self-produced polymeric matrix. It offers its members such benefits as an optimal microenvironment for growth, easy transmission of genes and resistance to antibiotics. Biofilm formation plays an essential role in pathogenesis of surgical site infections. Aim: The aim of the study was to assess whether there is a relationship between biofilm formation by Gram-positive cocci and complications following cardiac surgery. Material and methods : 44 Staphylococcus epidermidis and 27 Enterococcus spp. strains isolated from 84 patients treated in the cardiac surgery unit were investigated. Colony morpho- logy was studied on Congo Red Agar, according to Freeman’s method. Quantitative estimation of biofilm formation was performed by the method of Christensen. To determine the relationship between biofilm formation and complications following cardiac surgery such as mortality, bacteraemia, respiratory tract infections, subcutaneous infections and resternotomy, multiple logistic regression models were used. Results: 61% of S. epidermidis and 40.7% of Enterococcus spp. were slime-producing strains. The average optical densities of bacterial films for S. epidermidis and Enterococcus spp. were 1.013 ±0.739 and 0.233 ±0.075 respectively. Patients infected by slime-producing S. epidermidis strains were nearly 7 times more likely to develop subcutaneous infection (OR = 6.9, p = 0.105). Isolation of S. epidermidis or Enterococcus spp. positive in CRA test correlated with the frequency of subcutaneous infection following cardiac surgery (OR = 2.364, p = 0.209). Conclusions: The majority of investigated strains were slime producing. Biofilm formation was related to increased pathogenicity. Isolation of strains able to form biofilm may be related to the development of subcutaneous infection following cardiac surgery.